Revealing how intra- and inter-annual variability of carbon uptake (GPP) affects wood cell biomass in an eastern white pine forest. (1st February 2023) - Puchi, Paulina F; Khomik, Myroslava; Frigo, Davide; Arain, M Altaf; Fonti, Patrick; Arx, Georg von; Castagneri, Daniele
Abstract: Forests are major terrestrial carbon (C) sinks and play a crucial role in climate change mitigation. Despite extensive studies on forest C sequestration, the relationship between seasonal C uptake and its allocation to woody biomass is poorly understood. Here we used a novel dendro-anatomical approach to investigate the relationships between climate variability, C uptake, and woody biomass growth in an 80 year-old eastern white pine ( Pinus strobus ) plantation forest in Ontario, Canada. We used eddy covariance (EC) gross primary productivity (GPP) from 2003–2018 and woody biomass estimated from chronologies of cell wall area (CWA, a proxy for C storage in individual wood cells) and ring wall area (RWA) for earlywood (EW) and latewood (LW) from 1970–2018. Warm temperatures in early spring and high precipitation in mid-spring and summer positively and strongly affected GPP, while high temperature and high vapor pressure deficit in the summer had a negative effect. From 2003 to 2018, there was a steady increase in both GPP and woody cell biomass. Moreover, we found strong positive correlations between GPP and CWA both in EW (May—July GPP, r = 0.65) and LW (July—August GPP, r = 0.89). Strong positive correlations were also found between GPP and RWA both in EW and LW (April—September, r = ⩾ 0.79). All these associations were stronger than the association between annual GPP and tree-ring width ( r = 0.61) used in previous studies. By increasing the resolution of tree-ring analysis to xylem-cell level, we captured intra-annual variability in biomass accumulation. We demonstrated a strong control of seasonal C assimilation (source) over C accumulation in woody biomass at this site. Coupling high-resolution EC fluxes (GPP) and wood anatomical measurements can help to reduce existing uncertainties on C source-sink relationships, opening new perspectives in the study of the C cycle in forests.